Analysis of Construction Safety Management System Based on the Ministry of Public Works and Housing Regulation No.10 of 2021 (Case Study: Basement Construction Project of the Great Mosque of Serang City) - Asyiah, Siti; Ujianto, Rifky; Asy Syahid, Mush'ab 'Abdu; Setiawati, Dwi Novi; Damanik, Mariana Feronica; Syarahbil, Syarahbil (Jurnal Fondasi, 2025)
The Indonesian Government through the Minister of Public Works and Housing has recently issued Regulation Number 10 of 2021 concerning guidelines for the Construction Safety Management System (SMKK). This regulation must be implemented during construction as it is part of project planning and control. The objectives of this research are to analyze the level of influence of PUPR Ministerial Regulation No.10 of 2021 on improving SMKK implementation in the basement construction project of the Great Mosque of Serang City, to identify hazards that can cause accidents in the construction work, and to determine control action plans to reduce the risk level of accidents in the Serang City Grand Mosque basement construction work. The conclusion is that PUPR Ministerial Regulation No. 10 of 2021 concerning SMKK has a significant impact. This regulation emphasizes the importance of work safety in construction projects, including the Serang City Grand Mosque basement construction. By using the Hazard Identification, Risk Assessment, Risk Control Determination, and Opportunity (IBPRP) method, potential hazards can be identified for each type of work. The identification of work risks assessed with low risk level is 23 types of work (32.41%), medium risk level is 39 types of work (54.92%), and high risk level is 9 types of work (12.67%) from a total of 71 work risks. From the analysis of risk control identification using the IBPRP table, one high-risk level work was selected, namely the first floor structure work with the sub-work of formwork dismantling and risk identification of scaffolding collapse. The risk controls identified are using support pipes to strengthen the scaffolding and installing 2-layer railings on the scaffolding, conducting toolbox meetings, safety induction, job training, and ensuring the scaffolding is safe to use, and using PPE (safety shoes, safety helmet, vest, long-sleeved work clothes, gloves, and full body harness).